An Optimization Model for Container Capacity in New Sorong-Papua Port - Iwan Vanany; Duha Awaluddin Kurniatullah; Edi Jadmiko; Dody Hartanto; zulfiyah Musfiroh (IPTEK Journal of Proceedings Series, 2014)
The issue of the logistics system is an important issue for the state of Indonesia as an archipelago. Effort to distribute commodities to destinations across the island and attempted export of transport costs become cheaper and faster is a thing to be achieved by all parties including the government of Indonesia. Logistical problems in eastern Indonesia are more complex than the western part of Indonesia. For example, the cost of transport from eastern Indonesia is more expensive than the western part of Indonesia. Therefore, PELINDO II as the company seeks to make the country a new facility in the form of New-port that will replace the port of Sorong Sorong. New-Sorong port will be the largest port in Eastern Indonesia. This paper makes an optimization model with the goal of optimizing shipping container and determines how much capacity should be made to the port of New-Sorong.